Perceptions of Corporate Executives in the Adoption and Implementation of Integrated Reporting : Evidence from Malaysia - Joshi, Prem Lal; Sallehhuddin, Abdullah; Munusamy, Predeeban (Indian Journal of Finance, 2018)
Integrated reporting (IR) is steadily gaining momentum globally. Therefore,  the aim of this paper was to examine the executives' perspectives on  IR  in the Malaysian context  regarding their awareness, benefits, costs, training requirements apart from ascertaining  how  organizations are preparing themselves towards adoption and disclosure of the IR. Using a simple random sampling method, 150 companies listed on Bursa Malaysia agreed to participate in the survey, however, responses were received from 50 companies only. Derived from literature review, a questionnaire was used to collect the data during April-June 2017.  Majority of the respondents  were senior managers and managers from accounting and finance functions. The responses were measured on a Likert scale. The findings revealed that none of the surveyed companies had yet adopted IR as the new reporting tool, yet 56% of them were considering adopting IR due to potential derived benefits. In Malaysia, the level of knowledge about IR is still at a lower level due to users' general lack of familiarity with  the IR model. Therefore, training will benefit the companies' executives to increase their awareness and knowledge of IR gradually. This gives us positive and integrated thinking towards IR in Malaysia. The Malaysian Institute of Accountants (MIA) emerged as  the  leading  agency for enforcement of IR  and is to be made a mandatory requirement for financial reporting in Malaysia.  The study suggested  that future studies  may  be targeted to the executives who have primary responsibility for preparing IR, in addition to  focusing on determinants of IR adoption and implementations.